Effect of Percolation on the Water Use Efficiency of Paddy Crop - Jantan, Ramlee (1992)
Attention in this study is focussed on the evaluation of the effect of percolation on Water Use Efficiency computation. In addition, total water use, amount of water supplied, total water requirement at various stages of crop growth and Water Use Efficiency were also determined. Some findings on the factors affecting percolation were also done. Field and Laboratory experiments were conducted through two consecutive seasons. The results obtained in the wet season were 742 mm of water was needed for ET, while water needed for S&P was different between the plots. In the upstream plot S&P was 267.31mm, in the intermediate plot it was -105.36mm, and in the downstream plot it was -328.73mm. The irrigation water supplied was 576.51 mm to the upstream plot, the intermediate plot recorded was 602.01 mm and the downstream plot was 487.58 mm. The precipitation was 515 mm. During the dry season, Evapotranspiration was 670 mm, while S&P was higher than in the wet season. The upstream plot recorded 306.81 mm, the intermediate plot was 108.6 mm and the dowstream plot was -104.53 mm. Irrigation water required during this season was higher. It was 987.81 mm, 864.27 mm and 735.95 mm, respectively for the upstream, intermediate and downstream plots, while precipitation was 151 mm . Water use Efficiency was calculated by a modified equation which is (ET + SW + We) / (IR + RF). The WUE in dry season ranged from 70X to 90X and in the wet season was 70X to 95X. These results are high when a comparison is made with values of WUE using Wickham's formula.